Second Five Year Plan Summary - Planning Commission (Planning Commission, 1956)
This Report sets out the proposals of the Planning Commission for the Second Five Year Plan. The Plan was considered in draft by the National Development Council which passed the following Resolution on the 2nd May, 1956: “Having considered the Draft Second Five Year Plan, “The National Development Council places on record its general approval and acceptance of the objectives, priorities and programmes embodied in the Plan; and “Relying on the enthusiasm and support of the people; “Affirms the common determination of the Central Government and the Governments of all the States of the Union of India to carry out the Plan, and to improve upon the targets set out in it; and “Calls upon all the citizens of India to work wholeheartedly for the full and timely realisation of the tasks, targets and aims of the Second Five Year Plan.
Government of India Planning Commission